On laser desorption/ionization mass spectrometry of molybdenum disulfide 2D nanomaterial - O. A. Boryak; M. V. Kosevich; V. A. Pashynska; P. O. Kuzema; V. A. Karachevtsev (Хімія, фізика та технологія поверхні)
Mass spectrometric characterization of non-molecular nanomaterials has its distinctive features as compared to analysis of molecular substances. Namely, not an individual molecular ion, but a set of charged clusters is usually sputtered from solid inorganic nanomaterials under desorption/ionization conditions. As an example, laser desorption/ionization (LDI) mass spectra of 2D nanomaterial of molybdenum disulfide MoS2 dispersed to nanoflakes, recorded in the negative ion mode, contain a large set of clusters MoxSyOz– of varied composition. Standardized description of the mass spectra of this type, which may differ for MoS2 nanomaterials produced by various procedures, is not formed by now. In the present report, an approach to description of cluster-type LDI mass spectra of MoS2 is proposed, which accounts isotopic distribution of polyisotopic Mo and average masses of the groups of peaks corresponding to MoxSyOz clusters. The proposed approach is applied to interpret the LDI mass spectra of 2D nanomaterials produced by sonication of MoS2 powder aimed at its exfoliation to nanoflakes under different conditions. The elucidated similarity of the mass spectral patterns of the MoS2 nanoflakes produced by two types of ultrasound generating devices operating at 22 and 1700 kHz frequencies confirms the efficiency of both conditions in exfoliation of MoS2. Comparison of mass spectral patterns of the nanomaterials produced in pure water and with addition of ammonia revealed slight effect of ammonia on the clusters composition, namely the appearance of a number of new clusters which presumably incorporate nitrogen atoms. Detailed description of the LDI mass spectra of 2D nanomaterials derived from MoS2 may be useful in the development of applications of these nanomaterials in nanophotonics, optoelectronics, biosensing, photothermal therapy, and other related areas and nanotechnologies.